The essentials of teaching physical education curriculum, instruction, and assessment - Mitchell, Stephen A. 1959-; Walton-Fisette, Jennifer L. 1978-
"This book will help you develop physically literate individuals by providing a comprehensive, yet concise, guide to what is most important for quality teaching, specifically focusing on the following components that define teaching for learning. This book, split up in five parts, presents the fundamental elements for teaching physical education. Part I includes four chapters that focus on teaching for learning in physical education. Part II focuses on teaching to SHAPE America's National Standards & Grade-Level Outcomes for K-12 Physical Education (2014). Parts III and IV provide guidance for preservice and beginning teachers in terms of planning for, instruction for, and assessment of student learning. Part V discusses the importance of advocacy and professional development for new teachers as they seek to align their subject with whole-school goals. The book also includes advice from educators in the field and online resources, which includes a test package, presentation package, and supplemental activities"--Provided by publisher.
Ms. Camia (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Physical education and training -- Study and teaching -- United States; Physical education and training -- Curricula -- United States